Hypocalcification type amelogenesis imperfecta in permanent dentition in association with heavily worn primary teeth, gingival hyperplasia, hypodontia and impacted teeth - (:unkn) unknown (My University, 1999)
A female patient with hypocalcification type amelogenesis imperfecta in permanent dentition in association with heavily worn primary teeth, gingival hyperplasia, hypodontia and impacted teeth is presented.
Keywords: Female; Humans; Adolescent; Anodontia; Mothers; Pedigree; Dermatoglyphics; Dentition, Mixed; Amelogenesis Imperfecta; Gingival Hyperplasia; Tooth Attrition; Tooth, Impacted